Infrared Spectroscopy Evidence of Weak Interactions in Frustrated Lewis Pairs Formed by Tris(pentafluorophenyl)borane - Marques, Leandro Ramos; Ando, Rômulo Augusto (Chemphyschem, 2023)
Frustrated Lewis pairs (FLPs) have been widely investigated as promising catalysts due to their metal‐free feature and ability to activate small molecules. Since their discovery, many works have been investigating how these Lewis pairs (intermolecular pairs) are held together in an encounter complex. This prompted several studies based on theoretical investigations, but experimental ones are limited yet. In this communication we show evidence of weak intermolecular interactions between Lewis acids and Lewis bases, distinguishing the Lewis adduct from FLPs, by probing fluorine‐carbon vibrational modes using infrared spectroscopy. The main evidence is based on the band shifts occurring in FLPs due to weak hydrogen bonds between the hydrogen atoms of the Lewis base and the fluorine atoms of Lewis acid. Two well‐known frustrated Lewis pairs (FLPs) and a classical Lewis adduct (CLP) were studied by infrared spectroscopy aiming to probe intermolecular interactions that sustain the formation of the FLPs. The infrared bands associated with F−C bonds in the Lewis acid B(C6F5)3 were used as probes to observe the spectral changes accompanied by the Lewis pair formation. The calculated reduced density gradient (RDG) maps supported the main interactions originated from the H/F interactions in the FLPs.